(untitled) (Journal of Nepal Geological Society, 2021)
This is the full volume of the Abstracts from the STenth Nepal Geological Congress on “Geosciences for Sustainable Development and Prosperity”, 7 – 8 March 2021, Kathmandu, Nepal Journal of Nepal Geological Society, 2021, Vol. 61 (Sp. Issue)